Design, preparation and cutting performance of bionic cutting tools based on head microstructures of dung beetle. (October 2020) - You, Changtang; Zhao, Guolong; Chu, Xuyang; Zhou, Wei; Long, Yangyang; Lian, Yunsong
Highlights: The convexes of dung beetle head were investigated. Bionic cutting tools based on head microstructures of dung beetle were prepared. Performance of bionic cutting tools in dry cutting Ti6Al4V titanium alloy was studied. Abstract: Metal cutting plays an important role in modern machining industry, but the cutting tool wear strictly restricts the processing efficiency and tool lifetime. Some billions of years of evolutionary natural creatures have the anti-friction function that scientists are eager to have in their cutting tools. Thus, two kinds of bionic cutting tools were designed based on the surface structure of dung beetle head in this article. Moreover, such tools were fabricated with laser processing based on YS8 cemented carbide cutting inserts. Ti6Al4V dry cutting experiment was carried out at CA6136 turning machine by bionic cutting tool ( a p = 0.3 mm, f = 0.1 mm/r). The main cutting force of Tool1 decreased 30.41 % than the non-microstructure tool when the cutting speed v c is 20 m/min, and the average friction coefficient at the tool-chip interface of Tool2 decreased by 14.53 % at 60 m/min.